Lived expertise of the structurally disadvantaged: towards a more just participatory transport planning process - Anke Klaever; Vanessa Rösner; Sophia Becker; Viktoria Scheidler (Mobilities, 2024)
In response to the negative effects of the car-dominated transport sector, especially in urban areas, and wider attempts to tackle the climate crisis, cities are reallocating car-dominated areas to promote active mobility, leisure and urban green space. These reallocations often take an experimental character and are accompanied by participation processes. Increased citizen participation results from both a paradigm shift in urban planning and a discourse shift towards mobility justice, emphasizing procedural and recognitional aspects of the transport transition. However, participatory planning processes themselves are conflict-ridden. They are criticised for favouring a loud, priviliged minority. Based on the need for diverse knowledge for mobility justice, including lived expertise, this study examines reasons for (non-) participation among structurally disadvantaged groups in transport planning, using Berlin's Graefekiez neighbourhood as a case study. Focus groups were conducted with mobility-disabled people and women from a residential area with low socio-economic status. Our analysis revealed that non-participation was influenced by the feeling of being excluded and ignored. Simultaneously, the research format created was perceived as a welcoming space that better reflects the lived expertise of the neighbourhood and facilitates real exchange of perspectives. Based on this, recommendations are derived to improve participatory transport planning processes and the strengths of transdisciplinary projects.
Keywords: 380; Lived expertise; participatory planning; street-space reallocation; mobility justice; transport governance